Selene and Endymion on the marble relief from Celeia - Šmid, Katarina (Arheološki vestnik, 2017)
The article discusses a relief of Selene and Endymion on a marble slab found in the courtyard of Knežji dvorec (Princes’ Palace) in Celje (Cilli in German in the early literature). The best comparisons to Selene (half-naked, holding a whip or a sceptre) can be found on the remnants of Vespasianic wall-painting from Pompeii and Herculaneum, and partially also on the much later mosaic from Uthina. Endymion and Eros, on the other hand, are better compared to the so-called first class of Roman Endymion-sarcophagi, dating to around AD 120–180. On the right lateral side is a winged childish figure, holding a covered basket, who in my opinion most likely represents one of the Seasons in the form of Erotes that were especially widespread in the second half of the 2nd century. The marble slab was originally a constituent part of the base of a larger aedicula tomb. Vera Kolšek drew attention to a badly damaged relief of Rhea Silvia and Mars, immured as spolium in a residential house at Prešernova ulica 10 in Celje. Both narrative reliefs share almost identical dimensions and similar compositions, and last but not least, both pairs of lovers are occasionally found side by side on Roman funerary sculpture and could therefore be part of the same tomb – either on the left or right corner.